Metabolic complications resulting from the use of antiretroviral therapy in HIV-infected patients - Abrahams, Zulfa (Department of Medicine, 2017)
While antiretroviral therapy (ART) has extended the life expectancy of those infected with HIV, it is also associated with a number of metabolic complications, such as dysglycaemia, insulin resistance and lipodystrophy. Lipodystrophy is characterised by an increase in trunk fat (lipohypertrophy) and/or a decrease in limb fat (lipoatrophy). This thesis investigates the metabolic complications associated with ART, and develops simple anthropometric cut-points for identifying those with lipodystrophy. Data for this thesis comes from three datasets (a cross sectional study and two longitudinal studies), collected between 2007 and 2013. All datasets consisted of black HIV-infected men and women presenting to ART clinics in Cape Town. The same measurements were collected in all studies: anthropometry, self-reported lipodystrophy, dual-energy X-ray absorptiometry (DXA), blood pressure (BP), cholesterol and glucose. Longitudinal data were used to assess long-term ART exposure on BP, glycaemia, insulin secretion and anthropometric measures in women on ART. We found that weight, waist circumference, and waist-hip ratio increased, limb skinfold thickness decreased, and the proportion of participants with hypertension and diabetes increased. Longitudinal data was used to describe changes in body fat distribution over a 24 month period. We found that women gained more overall weight and more regional fat in all areas compared to men. The risk of lipoatrophy was two-fold greater in men than in women. Simple, objective measures to define lipoatrophy and lipohypertrophy by comparing patient report to anthropometric and DXA-derived variables, were developed using cross sectional data. In women, the best predictors of lipoatrophy were triceps and thigh skinfold thicknesses, and for lipohypertrophy it was waist/hip ratio. Longitudinal data was used to validate the objective measures that were developed by comparing change in limb fat and trunk fat as measured by DXA to anthropometric variables. We showed that the best predictors of lipoatrophy in women were hip and mid-thigh circumference, and mid-arm circumference in men. The thesis findings highlight the importance of early identification of these cardiometabolic risks in Africa. The development of anthropometric measures are of particular relevance in resource limited settings, where health professionals need simple and inexpensive methods for diagnosing patients with lipoatrophy and lipohypertrophy.